Toward Development of Inflatable Stents with Application in Endovascular Treatments. (23rd October 2018) - Amiri Moghadam, Amir Ali; Alaie, Seyedhamidreza; Gharaie, Saleh; Nath, Suborna Deb; Vawda, Sumayya; Al'Aref, Subhi J.; Romito, Eva A.; Kolli, Kranthi K.; Min, James K.; Dunham, Simon; Mosadegh, Bobak
Abstract: Although design and fabrication of metallic stents are extensively explored and established, the application of inflatable stents in endovascular treatments is relatively new. Inflatable stents introduce several advantages, such as repositionability and conformability to surrounding anatomic structures. These characteristics make the stent suitable for transcatheter treatment of cardiovascular diseases, such as valvular heart disease, and aortic aneurysms. This paper reports on a rapid and cost‐effective fabrication method, based on soft robotic technology, for the development of inflatable stents made of thermoplastic polyurethane. The stent is an inflatable cylinder that contains an array of bonded regions that form a continuous network, resembling a hexagonal lattice pattern. This pattern prevents the stent from buckling into an irregular shape upon inflation. The effect of this pattern on the maximum burst pressure, thickness, and pull‐out force of the stent is characterized. Finally, a trileaflet polyurethane valve is integrated into the inflatable stent frame to demonstrate its application as a transcatheter heart valve. This work serves as a proof of principle that inflatable stents can be useful in cardiovascular applications where conformability to surrounding tissue is advantageous, such as abdominal aortic aneurysm and aortic valve replacement. Abstract : The design and fabrication methods for engineering inflatable stents for cardiovascular applications is described herein. Various design and performance parameters are evaluated to serve as a proof‐of principle study for these novel cardiac devices. The use of soft materials and inflatable form factors in stented structures has promise to enable highly conformable cardiac devices that can be deployed via a catheter.